The Practice of Religious Moderation in Muhammadiyah Higher Education (A Case Study in The Hadith Studies Program at Ahmad Dahlan University) - Lathif, Parjiman (IJISH (International Journal of Islamic Studies and Humanities), 2024)
Religious moderation is an urgent necessity in the era of globalization to maintain social stability and interfaith harmony. Islamic-based higher education institutions, such as Ahmad Dahlan University, play a strategic role in shaping students' moderate and tolerant character. This study examines the practice of religious moderation in the Hadith Studies Program at Ahmad Dahlan University, aiming to understand how moderation values are applied in the academic environment and student life. This research employs a descriptive quantitative and causal approach using a survey method. The research population consists of students from the Hadith Studies Program at Ahmad Dahlan University, with a sample of 61 students selected through a simple random sampling technique. Data collection was conducted using a Likert-scale-based questionnaire to measure attitudes, understanding, and practices of religious moderation. The study reveals that students' attitudes toward religious moderation play a significant role in shaping moderate behaviors. Furthermore, a deep understanding of moderate religious values supports the effective implementation of religious moderation, while moderate religious practices enhance its application in daily life. The findings contribute to the development of religious moderation theory, demonstrating that students' attitudes, understanding, and practices have a substantial impact on moderating religious views. These insights can serve as a foundation for designing more effective educational programs aimed at fostering moderate attitudes and understanding among students.